2020
DOI: 10.1111/jpy.12956
|View full text |Cite
|
Sign up to set email alerts
|

Lobophora (Dictyotales) Species Richness, Ecology and Biogeography Across the NorthEastern Atlantic Archipelagos and Description of Two New Species1

Abstract: The brown alga Lobophora (Dictyotales, Phaeophyceae) is an important macroalga in the North‐eastern Atlantic archipelagos (i.e., Macaronesia). Notably in the Canaries it can dominate benthic assemblages. While the genus has been the subject of several ecological studies in the Canaries, no study has yet been conducted to assess species‐level diversity of Lobophora in Macaronesia. We reassessed the diversity of Lobophora in Macaronesia, reporting the presence of seven species (L. caboverdeana sp. nov., L. canar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…An additional species recently described from Cape Verde, L. caboverdeana (Vieira et al. 2019b), is reported from the Greater Caribbean for the first time. In addition, two lineages are newly reported for the Caribbean, L .…”
Section: Resultsmentioning
confidence: 86%
“…An additional species recently described from Cape Verde, L. caboverdeana (Vieira et al. 2019b), is reported from the Greater Caribbean for the first time. In addition, two lineages are newly reported for the Caribbean, L .…”
Section: Resultsmentioning
confidence: 86%
“…Photographs of the studied material were taken using a smart phone Samsung Galaxy S8 (SM-G950F). For the morphological identification specialized literature was used (Camacho et al, 2019;Godínez-Ortega et al, 2018;Schultz et al, 2015;Vieira et al, 2016;Vieira, Henriques et al, 2020;Vieira, Morrow et al, 2020). Once identified they were deposited in 95% EtOH in labeled bottles.…”
Section: Methodsmentioning
confidence: 99%
“…However, according to Vieira et al (2016), the genus Lobophora does not only display different morphological forms, but also can inhabit several ecological niches. Recent studies have demonstrated that the genus Lobophora is more diverse than historically stated (Camacho et al, 2019;Schultz et al, 2015;Sun et al, 2012;Vieira et al, 2016;Vieira, Henriques et al, 2020;Vieira, Morrow et al, 2020). These authors argued that different morphotypes and ecotypes can differentiate one species from another.…”
Section: Introductionmentioning
confidence: 97%
“…Recent molecular phylogenies of the genera Dictyota , Padina and Lobophora (Silberfeld et al., 2014; Tronholm, Steen et al., 2010; Vieira et al., 2017) revealed rampant cryptic diversity as well as high species diversity. At a local scale, various species of Dictyotales are able to co‐exist in sympatry by occupying micro‐niches (Vieira, Henriques, et al., 2020; Vieira, Morrow, et al., 2020; Tronholm, Sansón, et al, 2010), which correlates with the evolution of efficient physical and chemical defence strategies against herbivores (Cronin et al., 1997; Vieira et al., 2019). At larger spatial scales, the broad distributions of several species demonstrate the capacity for and importance of long‐distance dispersal in their evolutionary history (Silberfeld et al., 2014; Tronholm, Steen et al., 2010; Vieira et al., 2017).…”
Section: Introductionmentioning
confidence: 99%